2018
DOI: 10.4103/jhrs.jhrs_114_16
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic hysterolaparoscopy for evaluation of infertility: Our experience in a tertiary Care Hospital

Abstract: Objective:The objective of this study is to analyze the role of diagnostic hysterolaparoscopy (DHL) for evaluation of infertility in a tertiary care hospital.Materials and Methods:This retrospective study was conducted from July 2014 to June 2016.Results:Out of 151 patients, 58.28% and 41.72% had primary and secondary infertility, respectively. In primary infertility group 37.5% and in secondary infertility group 49.2% had abnormal findings. Most common finding was adnexal adhesions (pelvic inflammatory diseas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
21
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(28 citation statements)
references
References 16 publications
6
21
1
Order By: Relevance
“…In hysteroscopy, commonest intervention done was transcervical resection of septum which was 9% in both primary and secondary infertility followed by transcervical resection of myoma and polypectomy. 26,27,28 Conclusion:-…”
Section: Discussion:-mentioning
confidence: 93%
“…In hysteroscopy, commonest intervention done was transcervical resection of septum which was 9% in both primary and secondary infertility followed by transcervical resection of myoma and polypectomy. 26,27,28 Conclusion:-…”
Section: Discussion:-mentioning
confidence: 93%
“…3 WHO estimated that the prevalence of infertility ranges from 3.9% to 16.8% in India. 4 Incidence of female infertility is 45.67%, male infertility is 54.33% and may be both can get involved in some of cases, range varies from region to region. 5 The current evidence indicates 9% prevalence of infertility (of 12 months) with 56% couples seeking medical care in more developed and 51.2% in less developed countries.…”
Section: Introductionmentioning
confidence: 99%
“…Infertility is defined by WHO as a disease of the reproductive system defined by the failure to achieve a clinical pregnancy after 12 months or more of regular unprotected sexual intercourse. 1 The prevalence of infertility is about 10%-15% of reproductive age couples. 1 WHO also estimated that the prevalence of infertility ranges from 3.9% to 16.8% in India.…”
Section: Introductionmentioning
confidence: 99%
“…1 The prevalence of infertility is about 10%-15% of reproductive age couples. 1 WHO also estimated that the prevalence of infertility ranges from 3.9% to 16.8% in India. 1 As per the estimates from Indian census data 2001, 1991 and 1981, researchers showed that childlessness in India has risen up.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation